Seedlings of temperate rainforest conifer and angiosperm trees differ in leaf area display - Lusk, Christopher H. (Oxford University Press, 2012)
BACKGROUND AND AIMS: The contemporary relegation of conifers mainly to cold or infertile sites has been ascribed to low competitive ability, as a result of the hydraulic inefficiency of tracheids and their seedlings' initial dependence on small foliage areas. Here it is hypothesized that, in temperate rainforests, the larger leaves of angiosperms also reduce self-shading and thus enable display of larger effective foliage areas than the numerous small leaves of conifers. METHODS: This hypothesis was tested using 3-D modelling of plant architecture and structural equation modelling to compare self-shading and light interception potential of seedlings of six conifers and 12 angiosperm trees from temperate rainforests. The ratio of displayed leaf area to plant mass (LAR(d)) was used to indicate plant light interception potential: LAR(d) is the product of specific leaf area, leaf mass fraction, self-shading and leaf angle. RESULTS: Angiosperm seedlings self-shaded less than conifers, mainly because of differences in leaf number (more than leaf size), and on average their LAR(d) was about twice that of conifers. Although specific leaf area was the most pervasive influence on LAR(d), differences in self-shading also significantly influenced LAR(d) of large seedlings. CONCLUSIONS: The ability to deploy foliage in relatively few, large leaves is advantageous in minimizing self-shading and enhancing seedling light interception potential per unit of plant biomass. This study adds significantly to evidence that vegetative traits may be at least as important as reproductive innovations in explaining the success of angiosperms in productive environments where vegetation is structured by light competition.